Electrochemical Impedance Spectroscopy 2020
DOI: 10.5772/intechopen.94470
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Impedance Spectroscopy (EIS): A Review Study of Basic Aspects of the Corrosion Mechanism Applied to Steels

Abstract: AC impedance measurements have been applied for over twenty years in electrochemistry and physics to investigate the electrical properties of conductive materials and their interfaces using an external electrical impulse (VOLTAGE, V or CURRENT, I) as driving force. Furthermore, its application has recently appeared to be destined in the Biotechnology field as an effective tool for rapid microbiologic diagnosis of living organism in situ. However, there is no doubt that the electrochemical impedance spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 58 publications
3
36
0
Order By: Relevance
“…The low phase angle for the NiO­(OH) ED also highlighted favorable OER kinetics with the NiO­(OH) ED catalyst. , In the Bode plot of NiO­(OH) ED /NF and Ni­(OH) 2 /NF, two changes in the slopes (Figure S18) are further correlated with the two time constants of the Nyquist plot (Figures e and S17). Moreover, the typical Nyquist and Bode plots for NiO­(OH) ED /NF inferred a favorable electron transfer between the in-situ-constructed oxyhydroxide electrode–electrolyte interfacial layer controlled by a spontaneous charge and mass transfer mechanism. , …”
Section: Resultsmentioning
confidence: 94%
“…The low phase angle for the NiO­(OH) ED also highlighted favorable OER kinetics with the NiO­(OH) ED catalyst. , In the Bode plot of NiO­(OH) ED /NF and Ni­(OH) 2 /NF, two changes in the slopes (Figure S18) are further correlated with the two time constants of the Nyquist plot (Figures e and S17). Moreover, the typical Nyquist and Bode plots for NiO­(OH) ED /NF inferred a favorable electron transfer between the in-situ-constructed oxyhydroxide electrode–electrolyte interfacial layer controlled by a spontaneous charge and mass transfer mechanism. , …”
Section: Resultsmentioning
confidence: 94%
“…It allows determining the photo-induced charge separation efficiency and transmission rate. 81,82 The Nyquist curves showed that resistance decreased after adding TiO2 and upon exposure to visible light radiation (Fig. 5.a).…”
Section: 2electrochemical Activitymentioning
confidence: 99%
“…Several methods have been developed in the past to detect and/or quantify the presence of corrosion. Non-destructive techniques such as electrochemical impedance spectroscopy (EIS) [ 3 ], linear polarization resistance (LPR) [ 4 ], Ultrasonic measurement, Eddy current [ 5 ] and Electrical resistance (ER) [ 6 ] can measure the corrosion rate. These techniques are all single point measurements.…”
Section: Introductionmentioning
confidence: 99%